Brief integrated motivational intervention : a treatment manual for co-occurring mental health and substance use problems - Graham, Hermine L.; Copello, Alex, 1957-; Birchwood, M. J.; Griffith, Emma (Psychologist) (John Wiley & Sons, 2016)
Brief Integrated Motivational Intervention provides clinicians and specialist practitioners with a brief, evidence-based treatment approach for motivating clients, who have comorbid mental health and alcohol and drug misuse.-Combines CBT, motivational interviewing, and the authors' own cognitive- behavioural integrated treatment (C-BIT) to engage clients in meaningful dialogue for change -Utilizes the short 'window of opportunity' when clients are admitted to psychiatric hospital or have recently relapsed, and helps clinicians to maximize the potential of this 'teachable moment' -Helpful tools such as session-specific content, illustrative case material and easy-to-use worksheets facilitate implementation of the approach across a range of settings including inpatient, community, and residential -Developed by an expert team with many years of experience in both research and practice in the fields of psychosis and addiction.